Information Strategies in Indigenous Communities During the COVID-19 Pandemic. - Mu-Yen CHEN; Yueh-Lin TSAI (Journal of Nursing, 2022)
The COVID-19 pandemic has had an unprecedented impact on society, especially in densely populated areas. Schools have implemented distance learning, which has spawned many related problems. This paper focuses on the difficulties arising from the epidemic in indigenous communities and how appropriate information strategies may be used to solve these. Four main suggestions are provided to assist indigenous students and their teachers to protect themselves and learn during the pandemic and to ensure that educational goals are achieved.